2015
DOI: 10.1159/000441221
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Subclassification of Indeterminate (Thy-3) Thyroid Cytology into Thy-3a and Thy-3f

Abstract: Objectives: The British Thy system is a widely used classification system for reporting thyroid fine-needle aspiration (FNA) cytology. The Royal College of Pathologists in 2009 recommended the subdivision of the Thy-3 (indeterminate) category into Thy-3a (atypia) and Thy-3f (follicular neoplasm). Our objective was to examine the malignancy rates of Thy-3a and Thy-3f cases at our institution and to investigate whether the risk of malignancy in Thy-3a cases is reduced by FNA on a different occasion showing benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…A further analysis showed that among TIR3A and TIR3B there is no significant difference between patients with and those without cancer in terms of age (TIR-3A: 58.78 vs. 53.31 years, p = 0.31; TIR-3B: 50.68 vs. 52.33 years, p = 0.65), as already shown by Brophy et al [16] .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A further analysis showed that among TIR3A and TIR3B there is no significant difference between patients with and those without cancer in terms of age (TIR-3A: 58.78 vs. 53.31 years, p = 0.31; TIR-3B: 50.68 vs. 52.33 years, p = 0.65), as already shown by Brophy et al [16] .…”
Section: Discussionsupporting
confidence: 70%
“…• The TIR-3B (high-risk indeterminate lesion) subcategory included: -specimens with high cellularity in a monotonous and repetitive microfollicular/trabecular arrangement, with scant or absent colloid; -samples composed exclusively or almost exclusively of Hürthle cells [10] ; -samples characterized by nuclear alterations suggestive of papillary carcinoma, but too mild or focal to be included in the TIR-4 category [16] . The TIR-3B subcategory should have a frequency lower than 10% and its cancer risk between 20 and 30% [9] .…”
Section: Cytological Classificationmentioning
confidence: 99%
“…Our 7% malignancy rate is also below their 17% standard. At another similar institution, their Thy3a study [6] reported a higher incidence of Thy3a usage. This retrospective study of 748 thyroid nodules saw 109 being reported as Thy3a with a malignancy rate of 13.4%.…”
Section: Discussionmentioning
confidence: 91%
“…Consequently, even with ultrasound and cytological examination, the character of thyroid nodules remains uncertain in approximately 1 in 7 thyroid patients. When a cytologically indeterminate nodule has been identified by an expert cytopathologist, doubt exists that the risk of cancer can be sufficiently reduced to avoid surgery through repeat biopsy, review by a second cytopathologist, further subclassification of the indeterminate category, or correlation with thyroid nodule ultrasound classification …”
Section: Introductionmentioning
confidence: 99%